Pengembangan Multimedia E-Book Magic (E-Boma) Materi ASEAN Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VI Sekolah Dasar - Ayu Nila Wati; Yatim Riyanto; Waspodo Tjipto Subroto (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The learning process of class VI students at SD Negeri 2 Sidoharjo Lamongan, shows that the learning process requires innovation, especially in learning media to make it more interesting and can help students understand the concept of material and can improve student learning outcomes. Based on this, this study aims to determine and describe the results of the validity of learning tools, practicality, and effectiveness of Multimedia E-Book Magic (E-BOMA), in improving the learning outcomes of grade VI elementary school students. This research is a development research using a 4-D development model and testing the device using pre-test and post-test. The research was conducted in the academic year 2021/2022 with 15 students as research subjects, and data collection techniques used were tests, observations, and questionnaires. Pre-test and post-test data regarding concept understanding will be analyzed using t-test and described in descriptive quantitative form. The results of this study indicate that the feasibility of developing Multimedia E-Book Magic (E-BOMA) as a result of material expert validation has a very valid category with a value of 92%, and media expert validation is 90% while the practicality of Multimedia E-Book Magic (E-BOMA) is on average. teacher assessment is 92.18% and the average student response questionnaire is 96.5%. Learning can be said to be good, and the effectiveness of Multimedia E-Book Magic (E-BOMA) is seen from the results of student learning carried out before learning with an average of 45% of students who complete and after participating in learning to 96% of students who complete with grades 75. In essence, the Development of Multimedia E-Book Magic (E-BOMA) can help students to improve student learning outcomes.